Is body shaming predicting poor physical health and is there a gender difference? - Eva Lind Fells Elíasdóttir 1992- (2016)
The aim of this study was to examine whether body shame was predicting physical illnesses and negative self-reported physical health. Furthermore, the aim was to examine gender differences regarding body shame, physical illnesses and self-reported physical health. Participants were 92 students in Reykjavik University aged from 20-38. Data was gathered through a questionnaire. The questionnaire included questions about gender, age, self-reported physical health, body shame, and physical illness. The results of the study showed that women were more likely to self-report their health as poor than men. However, women were not more likely to score higher on the body shame scale and report physical illnesses than men. The results also showed that participants who scored high on the body shame scale were not more likely to report physical illnesses, nor were they more likely to self-report their physical health as poor. Keywords: body shame, physical illness, self-reported physical health Markmið þessarar rannsóknar var að kanna hvort að líkamleg skömm spáði fyrir um líkamleg veikindi og neikvætt sjálfsmat á líkamlegri heilsu. Jafnframt var markmiðið að kanna kynjamun varðandi líkamlega skömm, líkamleg veikindi og sjálfsmat á líkamlegri heilsu. Þátttakendur voru 92 nemendur við Háskólann í Reykjavík á aldrinum 20-38. Gagnaöflun fór fram með spurningalista. Spurningalistinn innihélt spurningar varðandi kyn, aldur, sjálfsmat á líkamlegri heilsu, líkamlega skömm og líkamleg veikindi. Niðurstöður rannsóknarinnar leiddu í ljós að konur voru líklegri til þess að meta sína eigin líkamlega heilsu verr heldur en karlar. Hins vegar voru konur ekki líklegri til þess að upplifa meiri líkamlega skömm og greina frá líkamlegum veikindum heldur en karlar. Niðurstöðurnar sýndu einnig að þátttakendur sem upplifðu meiri líkamlega skömm voru ekki líklegri til þess að greina frá líkamlegum veikindum, né voru þeir líklegri til að meta sína eigin líkamlega heilsu sem slæma. Lykilorð: líkamleg skömm, líkamleg veikindi, sjálfsmat á ...